Predicting Factors of Drop Out Counseling Process in University Psychological Counseling and Guidance Center - Omer OZER; Ahmet ALTINOK (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Objective: Objective: The purpose of this study is to evaluate the predicting factors the drop out the counseling process. Methods: The study group consists of 555 college students admitted to a Counseling and Guidance Center (CGC) and participated in at least one session of counseling after the first view in the 2013-2014 academic year. As a data collection tool, an “Application Form” on the demographic information and the “Brief Symptom Inventory” was applied to the students; and independent samples t-test and binary logistic regression techniques were used in the analysis of the collected data. Results: According to the analysis results, the age of the students attending the counseling process was found to be higher than those who drop out, but no significant difference was found in their psychometric properties in terms of continuation of the counseling process. Only the age of clients and their previous psychiatric help history was found to predict the dropping out counseling process early. Conclusion: Drop outs are less frequently observed in clients having a previous psychiatric help experience. In addition, it was determined that older clients less frequently drop out the counseling process